2018
DOI: 10.22454/fammed.2018.145163
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Preclinical Grading and USMLE Scores in US Allopathic Medical Schools

Abstract: Background and Objectives: Pass/fail preclinical grading is associated with improved student well-being. Studies do not demonstrate differences in United States Medical Licensing Examination (USMLE) scores after adopting pass/fail grading, but were conducted at unrepresentative, highly selective institutions, and average scores increased overall during the study periods. We investigated the effect of preclinical grading on USMLE scores across 96 US medical schools. Methods: Preclinical grading systems were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…In addition, other medical schools may have different curriculum than RVUCOM, so our predictive models may not apply to other medical schools. Some medical schools have converted to a pass/fail grading system recently [13], therefore our models may not work in schools with this new grading system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other medical schools may have different curriculum than RVUCOM, so our predictive models may not apply to other medical schools. Some medical schools have converted to a pass/fail grading system recently [13], therefore our models may not work in schools with this new grading system.…”
Section: Discussionmentioning
confidence: 99%
“…However, SED itself did not have a discernible effect on Step 2 CK scoring [ 3 ]. Pass/fail preclinical curriculum did not have a significant effect on Step 2 CK scoring [ 4 , 5 ]. Students participating in extracurricular activities, such as free clinic volunteering, were found to have higher Step 2 CK scores compared to their peers [ 6 ].…”
Section: Reviewmentioning
confidence: 99%
“…Some students may worry that admission to a medical institution with the tiered categorical grading scheme will be detrimental. We found that a pass/fail grading curriculum had no significant impact on Step 2 CK scoring [ 4 , 5 ]. However, individual preclinical examination grades did demonstrate a small effect size on Step 2 CK scoring [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, many medical schools have adopted a pass/fail system for pre-clinical years, which has been shown to improve the psychological well-being of medical students[ 6 ]. With the announcement that USMLE program will change the Step 1 score reporting from a three-digit numeric score to Pass/Fail only [ 7 ], LORs may become more important to identify ‘good fit’ anesthesiology residency candidates.…”
Section: Introductionmentioning
confidence: 99%